Abstracts in Japanese and Spanish of Scientific Articles in the Field of Medicine - Muñoz-Arias, E; Perello-Enrich, J; Hevia-Penna, P; Rubio-Martin, R (UNIV COMPLUTENSE MADRID, SERVICIO PUBLICACIONES, 2019)
In spite of the fact that there is no lack of studies on the rethorics about the structure of scientific abstracts, those studies centered both on Spanish and Japanese by themselves and those taken as a contrastive rethoric analysis are sparse or non-existent. In our investigation we propose a contrastive rethoric analysis based on Swales & Peak s rethoric move (2009), applied to abstracts of scientific articles of the Medicine field. These abstracts belonged to indexed journals and 10 of them were originally written in Japanese and the other 10 in Spanish. Results of the analysis show a clear difference between abstracts in Japanese and Spanish were in the latter their structure is more homogeneous, as all the moves analyzed appear more frequently than in Japanese. On the other hand, in both cases the moves backgrounds and objectives are preferred above methods, results and conclusions, which appear less frequently. This fact opens further research to reflect on the possible causes of this lack of coherence with the rethoric organization considered more appropriate. We conclude as well about the need to perform a more detailed analysis of the content of each move, making a differentiation some of the characteristics steps for, in every case, being able to arrive at deeper conclusions about the content and the privileged communicative intention, as well as expanding the research corpus both within the medical field and to other disciplines.